Effect on haemodynamic parameters following spinal anaesthesia in sitting versus left lateral position for lower segment caesarean section: a comparative study - Noorjahan; Binarani, Maharabam; M., Dhayanithy; Koyu, Sophia; Lollen, Lippi; K., Vigneshwaravibhava (International Journal of Research in Medical Sciences, 2024)
Background: The percentage of caesarean deliveries carried out under spinal anaesthesia has greatly increased over the last 20 years. However, hypotension remains the most common complication of spinal anaesthesia. Methods: The study groups divided into two, named group S and group L. The total sample size was 76, 38 patients in each group. All the patients were given 2 ml of hyperbaric bupivacaine (0.5%) in L3-4 midline intrathecal space in sitting position in group S, and in left lateral position in group L. Results: The comparison of heart rate showed that there was less heart rate fluctuation in group S. Statistically significant difference in mean systolic and diastolic blood pressure was seen between the groups during 2nd to 6th minutes, with more stability in group S. The mean MAP was found to be statistically significant in between 2 to 6 minutes and after 25 minutes. The mean onset time of hypotension in the group S was 17.07±7.98 minutes and that in the group L was 11.54±4.66 minutes. Conclusions: There were no significant differences in the time to reach sensory block level T6, degree of motor blockade (Bromage scale), neonatal outcome and complications in between the two groups. However onset of spinal anaesthesia is faster in the lateral position. Similarly hypotension is more in the left lateral position. The insignificant difference in block height could be because of adjustments in table position.